Hydroxychloroquine monotherapy in sarcoidosis: Indications, efficacy, and side effects - Vermeer, Britney; Veltkamp, Marcel; Raasing, Lisette Regina Maria; Wind, Anne Elisabeth; Vorselaars, Adriane Dore Marie (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2024)
Background and aim: In sarcoidosis which is not threatening vital internal organs such as heart, central nervous system or lungs immunomodulatory treatment, such as hydroxychloroquine can be considered. Despite its common use, limited data are available regarding effectiveness and side effects as monotherapy in sarcoidosis. Recommendations on its usage are based on expert opinion as literature is scarce. Methods: This retrospective study examines real-world data about the indications, effectivity and side effects of hydroxychloroquine monotherapy in sarcoidosis patients with no damage to the vital internal organs. Successful treatment was defined as continuation after 24 weeks without step up therapy or worsening of symptoms. Results: Sixty patients were eligible for the study. Starting dose was 400mg/day, lowered to 200mg/day after 3 months in most patients. The predominant treatment indications were musculoskeletal 45 (75%) and cutaneous involvement 13 (22%). Thirty-three patients (55%) continued treatment after 24 weeks. Twenty-four patients (40%) mentioned side effects, mainly gastrointestinal, leading to treatment discontinuation in eleven patients (18%). No severe side effects were seen. Continuation after 24 weeks was significantly higher in patients with cutaneous involvement compared to other indications 85% vs 47% respectively (p =0.02). Conclusions: Treatment with hydroxychloroquine monotherapy was satisfactory in 55% of patients, especially for cutaneous involvement. However, it poses considerable non-severe side-effects.